Occurrence and Dynamism of Lactic Acid Bacteria in Distinct Ecological Niches: A Multifaceted Functional Health Perspective - George, Fanny; Daniel, Catherine; Thomas, Muriel; Singer, Elisabeth; Guilbaud, Axel; Tessier, Frédéric J.; Revol-Junelles, Anne-Marie; Borges, Frédéric; Foligné, Benoît (Frontiers in Microbiology, 2018)
Lactic acid bacteria (LAB) are representative members of multiple ecosystems on earth, displaying dynamic interactions within animal and plant kingdoms in respect with other microbes. This highly heterogeneous phylogenetic group has co-evolved with plants, invertebrates and vertebrates, establishing either mutualism, symbiosis, commensalism and even parasitism-like behavior with their hosts. Depending on their location and environment conditions, LAB can be dominant or sometimes in minority within ecosystems. Whatever their origins and relative abundance in specific anatomic sites, LAB exhibit multifaceted ecological and functional properties. Whereas some resident LAB permanently inhabit distinct animal mucosal cavities, others are provided by food and may transiently occupy the gastro-intestinal tract. It is admitted that the overall gut microbiome has a deep impact on health and diseases. Here, we examined the presence and the physiological role of LAB in the healthy human and several animal microbiome. Moreover, we also highlighted some dysbiotic states and related consequences for health, considering both the resident and the so-called “transionts” microorganisms. Whether LAB-related health effects act collectively or following a strain-specificity dogma is also addressed. Besides the highly suggested contribution of LAB to interplay with immune, metabolic and even brain-axis regulation, the possible involvement of LAB in xenobiotic detoxification processes and metal equilibrium is also tackled. Recent technological developments such as functional metagenomic, metabolomic, high content screening and design in vitro and in vivo experimental models now open new horizons for LAB as markers applied for disease diagnosis, susceptibility and follow-up. Moreover, identification of general and more specific molecular mechanisms, based on antioxidant, antimicrobial, anti-inflammatory and detoxifying properties of LAB currently extends their selection and promising use, either as probiotics, traditional and functional foods, for dedicated treatments and mostly for maintenance of normobiosis and homeostasis.